Temporal patterning in neural progenitors: from Drosophila development to childhood cancers - Cédric Maurange (The Company of Biologists, 2020)
The developing central nervous system (CNS) is particularly prone to malignant transformation, but the underlying mechanisms remain unresolved. However, periods of tumor susceptibility appear to correlate with windows of increased proliferation, which are often observed during embryonic and fetal stages and reflect stereotypical changes in the proliferative properties of neural progenitors. The temporal mechanisms underlying these proliferation patterns are still unclear in mammals. In Drosophila, two decades of work have revealed a network of sequentially expressed transcription factors and RNA-binding proteins that compose a neural progenitor-intrinsic temporal patterning system. Temporal patterning controls both the identity of the post-mitotic progeny of neural progenitors, according to the order in which they arose, and the proliferative properties of neural progenitors along development. In addition, in Drosophila, temporal patterning delineates early windows of cancer susceptibility and is aberrantly regulated in developmental tumors to govern cellular hierarchy as well as the metabolic and proliferative heterogeneity of tumor cells. Whereas recent studies have shown that similar genetic programs unfold during both fetal development and pediatric brain tumors, I discuss, in this Review, how the concept of temporal patterning that was pioneered in Drosophila could help to understand the mechanisms of initiation and progression of CNS tumors in children.